FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MPASI DINI PADA BAYI USIA 0-6 BULAN DI DUSUN WALUYA DESA WALUYA KECAMATAN KUTAWALUYA KABUPATEN KARAWANG TAHUN 2023 - Nurazizah, Fitria Ulfah; Julianti, Neneng (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
MPASI is given to babies aged 6-24 months. In Indonesia, the prevalence of mothers who provide early MPASI is 12.6%. The aim of the research is to determine the factors associated with giving early MPASI to babies aged 0-6 months in Waluya Hamlet, Waluya Village, Kutawaluya District, Karawang Regency in 2023. This research method uses quantitative analytics with a cross sectional approach. The population was 167 mothers and the sample was 130 mothers using purposive sampling technique. The research instrument uses a questionnaire sheet. The analysis used univariate and bivariate analysis. Statistical tests used the chi-square test. Results of bivariate analysis on the variables knowledge (ρ= 0.042), education (ρ= 0.016), employment (ρ= 0.002), culture (ρ= 0.000) and the role of health workers (ρ= 0.030). The conclusion of this research is that there is a relationship between knowledge, education, work, culture and the role of health workers and providing early MPASI to babies aged 0-6 months. It is hoped that breastfeeding mothers can provide MPASI on time.